Rapid phase demodulation for projection fringe profilometry - Zhang, Zhun; Chen, Jian pei; Liu, Shengde; Li, Jin qian; Chen, Qi jie; Zhong, Li yun (Optik (Stuttgart), 2013)
To reconstruct 3D shape of large scale object rapidly, a novel phase demodulation approach for sinusoidal projection fringe is proposed. Firstly, a group of computer-generated normal sinusoidal fringe is projected to the reference plane and the measured object respectively, and then the corresponding sinusoidal fringe pattern on the reference plane and its deformed fringe pattern modulated by the measured object are captured by CCD. Secondly, the linear normalization algorithm is introduced to make the captured fringe normalization. Specially, using the phase slope notion, the reference phase slope and the modulated phase slope can be obtained by the direct phase recovery algorithm. Finally, based on the subtraction operation between the above two phase slopes, the phase distribution of the measured object can be obtained conveniently. Compared with the conventional Fourier transform profilometry and phase-shifting profilometry, in this proposed method, due to the calculation of phase demodulation is greatly simplified, thus the speed of 3D shape reconstruction is improved significantly. Importantly, this proposed method supplies a useful tool for the 3D shape reconstruction of large scale object.